Actinomyces turicensis: An unusual cause of cervicofacial actinomycosis presenting as ludwig angina in an immunocompromised host - Case report and literature review - Nirali Vassa; Ateeq Mubarik; Dharti Patel; Salman Muddassir (IDCases, 2019)
Actinomyces is an anaerobic, gram-positive bacillus that is known to cause chronic granulomatous infections. Common risk factors predisposing patients to this life-threatening infection are recent dental procedures, immunosuppression from malignancy, or history of smoking and alcohol use. Actinomyces, commonly found in the normal flora of the oral cavity, is one of the pathogens that can cause Ludwig’s angina. Ludwig's angina is diffuse cellulitis and edema of the soft tissues of the neck and floor of the mouth. Cervicofacial actinomyces is an invasive infection that can form life-threatening abscesses through its rapid spread. Actinomyces turicensis is an isolate that has emerged recently to cause infections in humans. There are few reported cases of this species causing abdominal and genital infections; however, there is no report of it invading the cervicofacial space. A feared complication of Ludwig’s angina and cervicofacial actinomyces is airway compromise. Therefore, prompt initiation of intravenous antibiotics is required for the treatment and prevention of deadly complications. We present a patient with left-sided neck swelling after a recent oral surgical procedure and was found to grow Actinomyces turicensis on wound culture. The patient was treated with intravenous ampicillin-sulbactam, which not only decreased the swelling but improved the necrotic appearance of his abscess wound. Keywords: Actinomyces, Actinomyces turicensis, Cervicofacial actinomycosis, Ludwig’s angina